2020
DOI: 10.1002/ggn2.10033
|View full text |Cite
|
Sign up to set email alerts
|

Active DNA demethylation—The epigenetic gatekeeper of development, immunity, and cancer

Abstract: DNA methylation is a critical process in the regulation of gene expression with dramatic effects in development and continually expanding roles in oncogenesis. 5-Methylcytosine was once considered to be an inherited and stably repressive epigenetic mark, which can be only removed by passive dilution during multiple rounds of DNA replication. However, in the past two decades, physiologically controlled DNA demethylation and deamination processes have been identified, thereby revealing the function of cytosine m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 222 publications
0
4
0
Order By: Relevance
“…Three mechanisms for demethylation have been identified: active demethylation (replication-independent), passive demethylation mediated by TET (replication-dependent), and 5mC deamination. In replication-independent active demethylation, TET dioxygenases oxidize 5mC to 5-hydroxymethylcytosine (5hmC), then to 5-formylcytosine (5fC), and finally to 5-carboxylcytosine (5caC) ( 20 ).…”
Section: Mechanism Of Dna Methylation and Dna Demethylationmentioning
confidence: 99%
“…Three mechanisms for demethylation have been identified: active demethylation (replication-independent), passive demethylation mediated by TET (replication-dependent), and 5mC deamination. In replication-independent active demethylation, TET dioxygenases oxidize 5mC to 5-hydroxymethylcytosine (5hmC), then to 5-formylcytosine (5fC), and finally to 5-carboxylcytosine (5caC) ( 20 ).…”
Section: Mechanism Of Dna Methylation and Dna Demethylationmentioning
confidence: 99%
“…Noteworthily, DNMT3A subcellular localization is not only nuclear, but has also been identified in the mitochondria where it may methylate mitochondrial DNA as well as in presynaptic MN terminals where its substrates and functions have not been identified yet [ 49 ]. If DNAm is a one-step process, demethylation instead requires multiple steps and involves several enzymatic players that are not all fully described, starting with an oxidation of the methyl residue by ten-eleven translocation enzymes (TETs) and leading to the formation of 5-hydroxymethylcytosine (5hmC, reviewed in [ 48 , 50 ]). While this contributes to view DNAm as the most stable and inheritable epigenetic mark, it should, however, be emphasized that DNAm is extremely dynamic with fast modulations occurring within the time frame of the circadian rhythm and slower modulations towards either hyper- or hypomethylation of CpG islands appearing over the entire lifespan (reviewed in [ 51 ]).…”
Section: Dna Methylationmentioning
confidence: 99%
“…These long-term dynamics permitted the emergence of the so-called DNAm clocks, which can acutely assess the chronological age of individuals, and reflects the combination of genetics, epigenetics, and environmental factors within their biological age [ 52 ]. In all, DNAm is a fundamental gene expression regulatory element, associated with physiological and pathological developmental processes as well as physiological and pathological aging [ 48 , 50 , 52 ].…”
Section: Dna Methylationmentioning
confidence: 99%
“…Numerous experimental and clinical data confirm that abnormalities in TET protein expression and function are closely associated with the development and progression of hematological malignancies [ 106 ]. The TET1 protein was first identified in patients with AML with chromosomal t (10; 11) (q22; q23) translocation, and TET1 is fused to the MLL gene [ 107 ]. Related studies have shown that TET1 binding to MLL leads to the upregulation of TET1 expression (overall increase in 5-hmC levels) and subsequent activation of signaling pathways such as Homeobox A (HOXA) 9, Meis homeobox 1 (Meis1), and pre-B-cell leukemia homeobox 3 (PBX3), which in turn promote the development and progression of MLL rearrangement leukemia [ 108 ].…”
Section: Ogt/tet Complexmentioning
confidence: 99%